Factors Affecting The Efficiency And Effectiveness Of Pharmaceutical Inventory Control Of IVF Services Using The Minimum-Maximum Stock Level (MMSL) Method - Prasasya Paramesthi; Sutopo Patria Jati; Antono Suryoputro (Green Publisher Indonesia, 2024)
Good control of the supply of drugs and consumables (BMHP) by Hospital Pharmaceutical Installations (IFRS) can avoid shortages or overstocks in pharmaceutical warehouses. The Type C